Hadith Interpretation from a Contemporary Perspective: Foundations, Techniques, and Its Relevance to the Dynamics of Modern Society. - Irmiani; Sitti Asiqah Usman Ali; Tasbih (Edumaspul: Jurnal Pendidikan, 2026)
Hadith is the second primary source of Islamic teachings after the Qur’an and serves to explain, elaborate, and provide concrete examples of Islamic values. Differences in temporal, social, cultural, and civilizational contexts between the Prophet Muhammad’s era and modern life require a methodological process of interpretation so that hadith can be understood accurately. This article examines the scientific foundations, interpretive techniques, and relevance of hadith interpretation in responding to contemporary social dynamics. The study employs library research by reviewing works on hadith sciences, usul al-fiqh, classical commentaries, and contemporary scholarship. The findings indicate that hadith interpretation must begin with verification of the chain of transmission and text, mastery of Arabic, understanding of asbab al-wurud and socio-historical context, integration with the Qur’an and related hadiths, and orientation toward maqasid al-shari‘ah. Interpretive techniques include textual, contextual, historical, linguistic, thematic, comparative, and carefully controlled hermeneutical approaches. These approaches preserve the authenticity of hadith while enabling its relevance to digital economy, artificial intelligence, bioethics, human rights, environmental issues, and plural societies. A comprehensive interpretation also prevents partial, rigid, and extreme readings of religious texts.